Polyaniline-coated charcoal ash: a novel high-capacity adsorbent for removal of thiocyanate ions from aqueous solutions - Gengec, Nevin Atalay; Ozbay, Bilge; Ozbay, Ismail; Kobya, Mehmet; Gengec, Erhan (Taylor & Francis Ltd, 2023)
Removal of thiocyanate (SCN-), which is widely used in many industrial processes is of concern due to this toxicity. In this work, the potential of polyaniline-coated charcoal ash (PANI-CCA) as a low-cost and efficient adsorbent was evaluated in order to remove thiocyanate ions from aqueous solution. Morphologies and chemical composition of the PANI-CCAhave been examined by using scanning electron microscopy and X-ray fluorescence spectrometry (XRD). Batch experiments were performed to examine the effects of operating conditions such as pH (6.0-10.0), ash dosage (0-0.30 g/50 ml), initial dye concentration (50-1500 mg/L), agitation period (2.5 min-24 hr) and temperature (25-60 C). The efficiency of adsorption process was evaluated by applyingLangmuir, Freundlich, Temkin and Halsey isotherm models. Among the performed isotherm models, Freundlich isotherm provided the best correlation for SCN ions onto PANI-CCAand the Freundlich constant related to the sorption capacity was calculated as 7.69 mg/g at an initial pH of 8.7 for the 50-1500 mg/L SCN- at 25 degrees C.Thermodynamic parameters were calculated as Delta G = 1.95-1.57 kJ/mol, Delta H = -4.66 kJ/mol, and Delta S = -0.0094 kJ/mol K at T = 288-333 K. The experimental data fitted well to the pseudo second-order kinetic model (r(2) = 0.999) and the kinetic model constants were calculated as k(2) = 0.1858-0.0185 g/mg min, h = 24.48-113.09 mg/g min and q(e,cal) = 12.16-78.19 mg/g at 50-500 mg/L of SCN- concentration. The negative values of isosteric enthalpy change, free energy change, and entropy change indicated an exothermic, spontaneous characteristics and decreasing disorder of the process, respectively.The overall results of the study demonstrated the good efficiency of PANI-CCA in adsorption of thiocyanate at compared to other adsorbents.
Keywords: Adsorption models; charcoal ash; polyaniline; thermodynamics; thiocyanate